(untitled) (Journal of Science and Engineering, 2026)
The Laxmi-Narasingh Temple, originally built in the 14th century on a square base with a two-tiered roof, holds significant historical and cultural value. In the 16th century, the temple underwent renovation, during which a semi-basement was added at the southeast corner of the lower plinth. This section houses a shrine to Tole Ganesha, an important figure which still has deep social and religious relevance for the local community. Photographic evidence from 1912 shows the temple in a severely deteriorated state, with only one storey remaining, marked by beautifully crafted central and side windows (ga-jhya). The temple was completely destroyed in the 1934 earthquake, leaving only the base structure (lakanshin) near the central entrance. The temple was reconstructed as a single-storey building with corrugated metal (CGI) roofing and metal-grilled doors on all four sides. This reconstruction was carried out in 1986 under the initiative of King Birendra Bir Bikram Shah Dev to commemorate the visit of Queen Elizabeth II. Further reconstruction work was later undertaken by Bhaktapur Municipality, in coordination with the Users’ Committee, heritage conservation experts, and engineers from Khwopa Engineering College and Khwopa College of Engineering. The restoration process involved studying several similar heritage structures as case studies and relied heavily on historical documents, remaining artifacts, traditional knowledge, and expert consultation. A reconstruction proposal by the late Surendra Joshi, a draughtsman involved in the Bhaktapur Development Project (BDP), also played a key role. This paper focuses on the importance of traditional iconography in restoring cultural monuments and discusses the challenges faced during the reconstruction. It also draws from interviews and literature reviews to explore various iconographic figures essential to the temple’s design especially for door portals, struts, windows and tympanum. The Laxmi-Narasingh Temple serves as a model example of heritage restoration, especially in situations where historical details are incomplete or unclear.